User Interface Design of Mobile Based E- Commerce Fasion Application (Shirtly) with Design Thinking Method - Rahmalia, Dea Puput (Journal of Applied Information System and Informatic (JAISI), 2024)
Technological advancements, particularly in the field of the internet, have brought about significant changes in the way people shop. In this context, “Shirtly,” a fashion store that provides a variety of products such as clothing, accessories, shoes, and jackets, seeks to develop a mobile-based e-commerce application to improve customers' shopping experience. This research aims to design an effective user interface (UI) by applying the Design Thinking method, which consists of five main steps: Empathize to understand user needs, Define to identify existing problems, Ideate to generate various creative ideas, Prototype to create an initial model of the application, and Test to test the prototype with users to get feedback. The results showed that the Shirtly application successfully met user expectations with a System Usability Scale (SUS) score of 88, which falls into the Excellent category. This finding confirms that the Design Thinking approach is very effective in designing user interfaces that are responsive and in accordance with user needs, so as to increase comfort and satisfaction in the online shopping experience. Thus, the Shirtly app is expected to not only attract more customers but also create a pleasant and efficient shopping experience. In addition, it is important for Shirtly to continuously iterate on the app design based on user feedback after launch. By utilizing user data analysis and regular customer satisfaction surveys, the development team can identify areas that need improvement and new features that users may want. This approach will not only help in maintaining customer loyalty but also enable Shirtly to remain competitive in the ever-evolving e-commerce market. With a focus on continuous innovation and adaptation to market trends and user preferences, the Shirtly app can become a superior and relevant online shopping platform in the eyes of consumers.